2019
DOI: 10.1103/physreve.99.013105
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis for a thermodynamically consistent model of relativistic fluid dynamics

Abstract: The search for thermodynamic admissibility moreover reveals a fundamental difference between liquids and gases in relativistic fluid dynamics, as the reversible convection mechanism is much simpler for liquids than for gases. In relativistic fluid mechanics, positive entropy production is known to be insufficient for guaranteeing stability. Much more restrictive criteria for thermodynamic admissibility have become available in nonequilibrium thermodynamics. We here perform a linear stability analysis for a mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…As it was shown in [8], non-relativistic SHTC equations can be viewed as a particular realization of the GENERIC formulation for non-equilibrium thermodynamics. It is, therefore, not surprising that the same heat conduction equations were also proposed by Öttinger [59][60][61] within the GENERIC approach in the relativistic context.…”
Section: (C) Heat Conductionmentioning
confidence: 54%
See 2 more Smart Citations
“…As it was shown in [8], non-relativistic SHTC equations can be viewed as a particular realization of the GENERIC formulation for non-equilibrium thermodynamics. It is, therefore, not surprising that the same heat conduction equations were also proposed by Öttinger [59][60][61] within the GENERIC approach in the relativistic context.…”
Section: (C) Heat Conductionmentioning
confidence: 54%
“…The irreversible part is represented by algebraic (no space and time derivatives) relaxation-type source terms and can be viewed as gradients of a dissipation potential intimately connected with the entropy, see [4]. We have observed that our variational formulation of the relativistic heat conduction is equivalent to the Hamiltonian formulation by Öttinger [34,32] within the GENERIC approach. The viscous part which is governed by the distortion evolution equation (40b) is different from that presented in [34,32].…”
Section: Numerical Examplesmentioning
confidence: 95%
See 1 more Smart Citation
“…Recall that the classical Navier-Stokes fluid dynamics can not be applied to modeling relativistic flows due to the intrinsic causality and stability issues of the Navier-Stokes equations [88]. To fix these issues of the classical fluid dynamics, several alternatives have been developed [74,66,54,97,40,37,98] to name just a few. The geometrical nature of our theory with the underlying Riemann-Cartan geometry also suggests that it would be not difficult to obtain the relativistic version of the theory which should fit well to the geometrical settings of the general relativity or its teleparallel equivalent [1].…”
Section: Discussionmentioning
confidence: 99%
“…By adding the heat flux, even nonisothermal rheology can be based on flux variables. Also the equations for relativistic hydrodynamics are usually based on flux variables [59][60][61][62][63][64][65][66] (see also article by Romenski, Peshkov, Dumbser and Fambri in this theme issue).…”
Section: Conclusion and Challengesmentioning
confidence: 99%